Ultra-Processed Food Exposure from Childhood to Young Adulthood: A Systematic Review of Obesity Risk, Cardiometabolic Dysregulation, and Emerging Biomarkers - Melisa Yuniarti; Anita Rahmiwati; Suci Destriatania (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2026)
Ultra-processed foods (UPFs) have become an increasingly prominent component of dietary patterns worldwide, especially among children, adolescents, and young adults. Accumulating evidence links high UPF consumption to obesity and cardiometabolic disorders, yet findings remain fragmented across developmental stages and outcome domains. This systematic literature review aimed to synthesize evidence on associations between UPF exposure from childhood through young adulthood and (i) overweight and obesity trajectories, (ii) cardiometabolic dysregulation, and (iii) emerging biomarkers of early metabolic risk. This systematic review was carried out following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. Peer-reviewed observational studies were identified through structured searches of Scopus and assessed for eligibility based on predefined criteria. Included studies primarily quantified UPF intake using the NOVA classification and reported obesity-related, cardiometabolic, or biomarker outcomes in youth and young adults. Due to heterogeneity in study design, populations, and exposure metrics, findings were synthesized narratively. Findings derived from both longitudinal and cross-sectional research consistently indicate that greater consumption of UPFs is linked to a higher likelihood of overweight and obesity across different stages of development, alongside adverse cardiometabolic profiles including impaired glucose homeostasis, dyslipidemia, inflammation, and altered appetite-regulating hormones. Emerging biomarkers, such as puberty sensitive indicators and nutritional status markers, suggested early biological perturbations linked to UPF intake. Structural determinants including food marketing, socioeconomic vulnerability, and food environments strongly shaped UPF exposure and modified health outcomes. Overall, UPF consumption across early life is consistently associated with metabolic risk, underscoring the need for life-course oriented, multi-level prevention strategies.